SANCTIONS FOR ANNULMENT OF MARRIAGE IN THE CUSTOMARY LAW OF THE PEKANBARU MALAY COMMUNITY - Juswandi; Akbarizan (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
The betrothal is conducted before the traditional marriage ceremony is carried out. Betrothal is commonly called an engagement or application process carried out by the male party to the female side. This research was conducted to determine the sanctions in the customary law of the Malay community that apply if one of the bride and groom's parties cancels the betrothal agreement and how the law is carried out. The research uses qualitative methods that are descriptive analysis. This study uses Schleiermacher's romantic hermeneutics, which is a text analysis approach. Based on the results of the research discussion, it can be concluded that the Malays uphold the rules and laws of Islamic sharia in marriage. In this study, there are two versions of customary sanctions adopted by the Malay community. The customary sanction applied in Kuantan Singingi Regency, Kuantan Hilir Seberang District, regarding the annulment of marriage is the agreement of both parties to provide a number of materials to one of the aggrieved parties so that there is no misunderstanding. This sanction is carried out in order to have a deterrent effect on the party who breaks the promise or cancels the marriage.